Evolution of the OmpR regulon in Salmonella enterica serovar Typhimurium and Escherichia coli in response to low pH - Quinn, Heather J. (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2013)
Two-component systems (TCS) enable bacteria to sense, respond and adapt to a wide range of environmental stimuli. The OmpR/EnvZ TCS is composed of the inner membrane sensor kinase EnvZ and the response regulator OmpR. In Escherichia coli (E. coli) EnvZ is stimulated by changes in osmotic pressure; EnvZ phosphorylates the transcription factor OmpR, which differentially expresses the outer membrane porins ompF and ompC. Comparatively, the orthologous OmpR/EnvZ TCS in Salmonella enterica serovar Typhimurium (S. Typhimurium) does not respond to osmolarity. Instead, studies have shown the ompR gene is activated by low pH and is essential for the expression of pathogenicity genes. These findings raised the question does ompR in E. coli respond to low pH?
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.